Exercises based on the phosphogenic energy system to develop the ability to perform with precision and accuracy - Diana Hussein Dr. Suhad Qassim (physical education and sport sciences college for women/ Baghdad University, 2020)
Each sport has its own energy requirements that differ from the energy requirements of other sports, and a different method is used in each of them, so the trainer must first rely on the principle of privacy in training first, that is, privacy according to the working energy system, that is, he defines the controlling energy system In that event, and how the muscles use the available energy to perform according to the energy production systems. As we find the serving skill is the first volleyball skill with which the team starts the match in order to be able to gain points directly, through knowledge it turns out that there is a weakness in the skill performance, especially the skill of serving and being The key to victory for volleyball players. This weakness may be attributed to the weakness or variation in the physical abilities of volleyball players Therefore, the two researchers decided to develop physical exercises according to the phosphogenic energy system, considering the volleyball game within the ATP-CP system)) Adenosine Triphosphate and Creatine Phosphate to prepare for physical performance within the game and to know the effect of these exercises on the performance of the skill of sending with volleyball